Sistem nota guru: Kajian kes di Sekolah Menengah Kebangsaan Tengku Ampuan Jemaah, Pelabuhan Klang / Norhaslinda Mahamud - Norhaslinda, Mahamud (2002)
The rapid development of computer and industry, nowadays becoming the main area for every person to compete. Preparing easy and aspect become the main choice in producing work that more productivity that have quality with the best work performance. This positive development is helping to increase the quality of management including notes management in school. The System of Teacher's Notes that I developed is to help the staff that assign to do a duty smoothly and to solve the problem while using design to fulfill all the needed that exist in the flowing of notes preparation. The preparing of the working system that more productive will help the staff in handling the management or notes, solving problem or the data redundancy and preparing the notes report neatly and fast. The using or Teacher's Notes System protected the system from the non-register with preparing of security system. This Teacher's Notes System also help the staff in updating data with suitable time.